<span>3(x + 5) = 2(3x + 18)
Use the distributive property:
3(x)+5(3)=2(3x)+18(2)
Simplify:
3x+15=6x+36
6x+36=3x+15
3x+36=15
3x=-21
x=-7
Check answer:
3(-7+5)=2(-21+18)
3(-2)=2(-3)
-6=-6
Hope this helps :)
</span>
Answer:
628
Step-by-step explanation:
So the formula is πr^2h/3
So the height is 6
pie is 3.14
Substitute:
3.14(10)^2 6/3
3.14(100)(2)
3.14(200)
628
Answer:
the last one (bottom right)
Step-by-step explanation:
4×pi is the same as twice around the whole circle to the beginning. it is the same as 0°, and cos(0) = 1, and then -2×cos(0) = -2
so, we only need to look, where the function reaches -2.
it should be at x = 0, x = 0.5 and x = 1.
Answer:
x = −2
Step-by-step explanation:
the steps are super long but this is the answer
The customer drawing a 30% discount card then the next customer 20% discount card has a probability of 5/40 for the 30% which = 12.5% and 20% is 15/40 which = 37.5% add them together then divide by 2 for a total of 25%.
The customer drawing a 10% card has a 20/40 which = 50% then a customer drawing a 20% card is 15/40 = 37.5% add them together then divide by 2 = 43.75%
The customer drawing a 10% card has a 20/40 which is 50%. Then another customer drawing another 10% is another 50% add them together and divide by 2 = 50%
The customer drawing a 20% card has a 5/40 which is 12.5% and another customer drawing a 20% card again is 12.5%. Add together and divide by 2 = 12.5%. So your answer is the 1st three.